New horizons in higher education: Realistic simulation as a teaching method (Research, Society and Development, 2021)
Objective: to report the author's experience with the realistic simulation developed with nursing students in the discipline of Semiology and Semiotechnics of the undergraduate course. Description of the experience: the simulations always took place in the nursing practice laboratory, three times a week, after an expository-dialog class about a certain content. They were guided by the teachers of the discipline. Five classes participated in the simulations, totaling 30 students. Immediately after the end of the simulations, a reflexive discussion (debriefing) was carried out, which allowed the assimilation of practices and the reconstruction of conducts. This methodology provided the students with greater security and confidence to perform nursing care for patients. Conclusion: The use of realistic simulation proved to be effective, with positive results on the improvement of knowledge, self-confidence, satisfaction with learning, providing greater association between theory and practice by providing experiences of situations that simulated reality.